The Effect of Women's Savings and Loans (SPP) in Improving the Economy and Family Income in the District Dolok Masihul, Serdang Bedagai Regency. - Suwadi Suwadi; Ari Syahputra (Institute of Computer Science (IOCS), 2021)
PNPM-MP is a program in which there are Women's Infrastructure and Savings and Loans (SPP) activities which are managed by the Activity Management Unit (UPK). SPP is one type of activity that clearly shows the seriousness of prioritizing Women's Empowerment. This study aims to analyze the effect of SPP Capital Loans in improving the economy and family income in Dolok Masihul District, Serdang Bedagai Regency. The population in this study were members of the Village/Kelurahan SPP Group in Dolok Masihul District. The type of research that the author uses is descriptive quantitative research, namely research that has the intent and purpose to analyze and provide data as accurately as possible about humans or other conditions or symptoms.Sampling for research according to Suharsimi Arikunto (2010: 112), if the subject is less than 100 people should be taken altogether, if the subject is large or more than 100 people can be taken 10-15% or 20-25% or more. The sampling technique used is the simple proportioned cluster sampling technique with a sample size of 20% of the total population, which is 60 samples. The results of testing hypothesis 1, it is known that tcount (1.506) > ttable (1.694), as well as the significance value of 0.142 > 0.05, it can be concluded that the SPP Savings and Loans Capital Loan Variable (X) has no significant effect on the Variables of Economic Improvement and Income Family (Y). Testing hypothesis 2, it is known that tcount (12.494) > ttable (1.672), as well as the significance value of 0.00 <0.05, it can be concluded that the hypothesis is accepted, meaning that the SPP Loan Variable (X) has an effect on the Family Income Variable (Y2).